VERIFICATION OF 235U BY USING MCNP CODE WITH COMPARISON MGAU ANALYSIS SOFTWARE FOR DEPLETED AND ENTRUSTMENT URANIUM - S. Makhlouf, Howaida Mansour, Atef El-Taher (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The current research was based on non-devastating measurements of gamma radiation. There are two samples under investigation which are depleted and enriched uranium. the obtained results that depended on MCNP-5 were in great understandings with the pronounced values inside the evaluated relative precision. the researchers can declare that, the Monte Carlo method fits the measurement conditions of the inspector. The relative accuracy obtained from MGAU were (0.447 and 0.187%) and (3.3 and 15.9%) for enriched uranium and depleted uranium, respectively